Balance Abilities and Kinesiophobia in Women with Fibromyalgia Syndrome: A Cross-Sectional Comparative Study - Zafer Yıldır, Cem; Berk, Ejder; Nacitarhan, Vedat; Koçyiğit, Burhan Fatih; Koca, Tuba Tülay; Demirel, Adnan (Archives of Rheumatology, 2025)
Background/Aims: This study evaluated balance performance and kinesiophobia levels between fibromyalgia syndrome patients and healthy controls to establish their relationship. Materials and Methods: Sixty female patients diagnosed with fibromyalgia and 60 healthy volunteers who did not have the condition were included in the study. The Fibromyalgia Impact Questionnaire was applied to the participants to evaluate the disease activity, and the Tampa Kinesophobia Scale was used for the evaluation of kinesiophobia. The four-square stepping test (FSST), functional reach test, timed up and go test (TUG), and posturography device were used to evaluate balance. The Mann–Whitney U test was used for comparing continuous variables between groups, the chi-square test for categorical variables, and Spearman’s rank correlation for examining relationships between parameters, with significance set at P < .05. Results: The fibromyalgia syndrome patients demonstrated significantly impaired balance abilities and elevated kinesiophobia scores compared to control subjects (P < .001). The FMS group experienced significantly more falls during the 6-month period than the control group, which had no falls (P < .001). Fall distribution showed that 30 patients (50%) experienced falls, with 18 patients having 1 fall, 8 patients having 2 falls, and 4 patients having ≥3 falls. Of the 60 FMS patients, 50 (83.3%) used medications with various combinations. The Tampa Scale for Kinesiophobia scores showed a statistically significant relationship with Fibromyalgia Impact Questionnaire scores (r: 0.507, P < .001). The balance parameters and kinesiophobia scores of FMS patients were both impaired, yet no significant relationship existed between these 2 measures (r values ranging from 0.08 to 0.15, all P > .05). Clinical balance tests (TUG, FSST) and most posturographic parameters failed to show any statistical connection with FMS disease activity. Conclusion: The results showed that female FMS patients had significantly impaired balance and higher kinesiophobia scores than healthy controls. These results show that balance impairments and kinesiophobia are both present in FMS, but they seem to be different aspects of the condition rather than directly related. Both factors should be assessed independently in clinical evaluation. Future research should investigate the mechanisms of these separate but co-occurring impairments in FMS.